Evaluasi dan Optimasi Desain Casing Sumur Pemboran dengan Metode Maximum Load di Sumur ENN-1 di Lapangan Batuwangi - Aly Rasyid; Edy Soesanto; Ezrawati Nunut Nababan (JURNAL BHARA PETRO ENERGI, 2022)
Batuwangi is field that positioned ini the Sumatera at southeastern part. Batuwangi is in the development stage. The ENN-1 is one of well at Batuwangi field, placed at the geographical coordinates 5˚25'21.24063 South Latitude and 106˚18'55.73957 East Longitude. ENN-1 is drilled as a directional well spud on December 9, 2014 and completed on February 6, 2015. ENN-1 well has a TD (total depth) of 3804 ftMD and 3247 SSTVD, as an oil producer. In this paper, it will be studied the planning of casing utilized in the ENN-1 well, to see whether the desain of casing is already the most technically choice or not, to do calibration evaluation the grade casing used in ENN- 1 Well. To perform evaluation, the Maximum Load method will be used, the case will be choosen against desain factors of burst, collapse, and tension load resistant of casing. Based on the evaluation of the study, it is found that casing grade in the ENN-1 Well is exceeds the technical requirement. That fact, need to be corrected since it will lead to cost inefficient, it will much more expensive, since the casing purchased is higher than technical requirement. Therefore, in this studied offer the casing grade proposal to be utilized in the ENN-1 well which meet with technical requirement as well as economically much more efficient than current design.